The influence of gender and SPM's mathematics grade towards the students' achievement in mathematics at UiTM Terengganu / Ruzaidah A. Rashid ... [et al.] - A. Rashid, Ruzaidah; Mohamed, Zamzulani; Muda @ Yusof, Nazuha; Abdul Karim, Zokree (Universiti Teknologi MARA, Kedah, 2021)
This paper aims to investigate gender performance in mathematics among students at UiTM Terengganu and also to determine the relationship between students' achievement in mathematics and Mathematics grade in Sijil Pelajaran Malaysia (SPM). The data was collected randomly from 86 students who took Business Mathematics course in 2018 through distribution of questionnaires. Descriptive analysis was used to overview the students' profile. Meanwhile, the Independent t-test and Spearman Rank Correlation were used in inferential analysis. The findings concluded that there was no significant difference in students' mathematics achievement between gender for this course. However, there was a significant positive relationship between mathematics achievement and Mathematics grade among students. As a conclusion, special attention must be given to the students who scored minimum grade in Mathematics at SPM level so that they can perform well at tertiary level.